MODUL ASUHAN KEPERAWATAN BERDASARKAN EVIDENCE BASED PRACTICE (EBP) : Intervensi Inovasi Untuk Menurunkan Length Of Stay (LOS) Pasien Dengan Gangguan Sistem Respirasi Di Intensive Care Unit (ICU) - Siti Hidayatun Nazza Darmansyah (2021)
NURSING CARE MODULE BASED ON EVIDENCE BASED PRACTICE (EBP): INNOVATION INTERVENTIONS TO REDUCE LENGTH OF STAY (LOS) PATIENTS WITH RESPIRATION SYSTEM DISORDERS IN THE INTENSIVE CARE UNIT (ICU) Siti Hidayatun Nazza D. The function of the respiratory system aims to obtain oxygen from the air to body tissues and remove carbon dioxide (Guyton et al, 2006). Whereas in patients with respiratory system disorders there are difficulties in this regard. Based on data in the journal (Juniarty J. P. Nainggolan et al, 2017) the most respiratory disorders in the ICU that cause death include pneumonia and ARDS (acute respiratory distress syndrome). The prevalence of pneumonia was 25 people (71.4%) and ARDS was 1 person (2.8%). Hospital acquired pneumonia (HAP) is the incidence of pneumonia 48 hours or more after the patient is admitted to the hospital. HAP is the second most common cause of patient infection in hospitals, and as the leading cause of death due to infection (mortality-rate around 30-70%), it is estimated that 27-50% are directly related to pneumonia (Warganegara, 2017). Ventilator acquired pneumonia (VAP) is one of the HAIs (Healthcare Associated Infections) that are often found in hospitals and includes pneumonia infections diagnosed after 48 hours of mechanical ventilation, both endotracheal tube and tracheostomy (Kemenkes RI, 2017). Based on the description above, researchers are interested in conducting research on effective nursing plans to address nursing problems in patients with respiratory system disorders in the ICU in order to improve the quality of life of patients during treatment. Keywords: ICU, ARDS, Ventilator acquired pneumonia (VAP)